Serving hotel customers in a postpandemic world : how can Hilton Worldwide recover and change? - Jia, Yankun, (SAGE Business cases., 2022)
Hotel occupancy rates plummeted during the COVID-19 pandemic. Hilton Worldwide CEO Chris Nassetta needed to strategize how the second largest global hotel chain could modify its business operations to fulfill guest expectations over the next year and in the post-pandemic world. The onset of an airborne virus known as COVID-19 brought the day-to-day operations of Hilton Worldwide, alongside other hospitality providers, to a screeching halt. To contain the virus, health and government officials recommended people only leave home for essential items. This strategy, while effective, burdened nearly every organization globally. Many businesses were forced to lay off their staff, leading to widespread economic uncertainty, and an unpredictable future for Hilton. Nassetta knew his company would need both short- and long-term goals to regain its footing and chart a way forward in a world where another virus or another calamity would likely strike again.